DERAJAT PERSAINGAN IINDUSTRI PERBANKAN INDONESIA: SETELAH KRISIS EKONOMI - Sri Yani Kusumastuti (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This paper analyses the influence of economic crisis and the subsequent reforms on the oligopolistic nature of the Indonesian banking industry. Since the crisis, there have beensubstantial changes in competitive environment. How did these changes affect a banking industry in which the three teen largest banks accounted for over 70 per cent of market share? To estimate the degree of competition, we apply Bresnahan’s (1989) conjectural variation model. Using estimation models based on microeconomic foundations, this method allows us to derive the index of the firm’s market power that is calculated as the deviation of the market piece from the marginal coat as known as Lerner index. The estimated indicates that the Lerner index showed a rising trend in the post-crisis period. This result indicates the possibility of a decline in the degree of competition.